Програма силової підготовки спортсменів у веслуванні академічному з використанням спеціальних тренажерів - Чжао Дун; Русанова, Ольга Михайлівна; Дяченко, Андрій Юрійович; Dong, Zhao; Rusanova, Olha; Dyachenko, Andriy (Східноєвропейський національний університет імені Лесі Українки, 2018)
У статті обґрунтовано можливості спеціальної силової підготовки спортсменів в академічній школі з використанням спеціальних тренажерів. Мета статті – оцінити вплив програми силової підготовки веслярів на підвищення спеціальної роботоздатності спортсменів у веслуванні академічному. Обладнання – ергометри для веслування академічного Concept 2 Dyno (силовий тренажер) і Concept 2. У дослідження взяли участь 14 кваліфікованих спортсменів-веслувальників віком від 19 до 24 років, майстри спорту та кандидати в майстри спорту. Доведено, що актуальним напрямом підвищення ефективності спеціальної силової підготовки спортсменів у веслуванні академічному є застосування силових вправ, які враховують специфіку гребних локомоцій і специфічні режими роботи м’язових груп. Для досягнення мети роботи розроблено програму спеціальної силової підготовки спортсменів у веслуванні академічному. Програма включає вправи на веслувальному силовому ергометрі Concept 2 Dyno. Режими роботи передбачають виконання рухів руками й ногами відповідно до структури веслових локомоцій. Під впливом спеціальних вправ на весловому силовому ергометрі Concept 2 Dyno у веслярів збільшилися силові характеристики роботи ногами та руками, на 6,2 і 2,5 % (тяга руками) та 6,0 і 2,7 % (жим ногами). Показано вплив спеціальних вправ на гребному силовому ергометрі Concept 2 Dyno на прояв спеціальної працездатності веслярів. Покращилися дані подолання стартового відрізка змагальної дистанції 500 м, показники спеціальної працездатності збільшилися на 2,5 % (ергометрична потужність) та на 1,1 % знизився час подолання відрізка. Показники спеціальної працездатності в модельних умовах подолання дистанції 2000 м на Concept 2 збільшилися, на 7,1 % (ергометрична потужність), на 2,9 % знизився час подолання дистанції. The article substantiates the possibilities of special strength training of athletes in an academic school with the use of special training simulators. The objective is to evaluate the effect of the program of strength training of the rowers on increasing the special ability of athletes in the academic rowing. Equipment: ergometers for the drilling of the academic Concept 2 Dyno (power simulator) and Concept 2. The study involved 14 skilled athletes - rowers aged from 19 to 24 years old, the masters of sports and candidates for the master of sports. It is shown that the use of strength exercises which take into account the specifics of rowing locomotion and the specific modes of operation of muscle groups, is an actual direction of increasing the effectiveness of special strength training of athletes in rowing. In order to achieve the goal of the work, a program of special strength training for athletes in rowing was developed. The program includes exercises on the rowing force ergometer Concept 2 Dyno. Modes of work include the implementation of movements of hands and feet in accordance with the structure of rowing locomotion. Under the influence of special exercises on the rowing power ergometer Concept 2 Dyno, the rowers increased the power characteristics of the legs and hands, respectively, by 6,2 % and 2,5 % (traction with their hands) and 6.0 and 2,7 % (bench press). The influence of special exercises on the rowing power ergometer Concept 2 Dyno on the manifestation of the special performance of oarsmen is shown. The parameters of overcoming the starting segment of the competitive distance of 500 m have improved, the indicators of special working capacity have increased by 2,5 % (ergometric power) and by 1,1 % the time for overcoming the segment has decreased. The parameters of special working capacity in the model conditions of overcoming the distance of 2000 m on the Concept 2 increased – 7,1 % (ergometric’ power), the time to overcome the distance decreased by 2,9 %.
The Program of Strength Training of Athletes in Academic Rowing with the Use of Special Training Simulators
Keywords: спеціальні тренажери; силовий ергометр Concept 2 Dyno; силові можливості; спеціальні силові вправи; веслування академічне; special simulators; power ergometer Concept 2 Dyno; power capabilities; special strength exercises; academic rowing